Biventricular Noncompaction Cardiomyopathy in a Patient Presenting with New Onset Seizure: Case Report - Oghenerukevwe Odiete; Ramanna Nagendra; Mark A. Lawson; Henry Okafor (Case Reports in Cardiology)
Ventricular noncompaction (VNC) of the myocardium is a rare genetic cardiomyopathy caused by a disorder during endocardial morphogenesis and could be accompanied by life-threatening complications. The major clinical manifestations of VNC are heart failure, arrhythmias, and embolic events. The left ventricle is the most commonly reported affected site, but a few cases of right ventricular involvement have also been reported. We report a case of biventricular noncompaction cardiomyopathy in a 31-year-old woman presenting with a new onset seizure. On the second day of her telemetry-monitored hospitalization, she suffered a witnessed ventricular fibrillation arrest requiring emergency direct-current cardioversion and induced hypothermia. Transthoracic echocardiography (TTE) showed isolated left ventricular (LV) noncompaction and depressed LV systolic function. Subsequent cardiac magnetic resonance imaging (MRI) revealed both left and right ventricular noncompaction. This unusual presentation highlights the importance of a complete and thorough evaluation of patients even when presenting with apparently noncardiac symptom(s).